Coal Energy in Energy Consumption: An Empirical Analysis in the Case of Russia and Türkiye - Huseynli, Bahman (International Journal of Energy Economics and Policy, 2024)
Coal, the fundamental element of the industrial revolution, is widely used for energy production in many countries. The use of coal in energy production continues in countries that have coal reserves, as well as in countries that are rapidly transitioning to renewable energy production. The aim of this study is to investigate the causal relationship between coal production and general energy consumption in Russia and Türkiye, which are among the countries that consume heavy coal. In the article, the relationship between the variables in these countries was tested with Granger causality analysis. According to the results of the analysis, it was determined that there was a one-sided causality relationship from coal production to energy consumption in Russia. When the findings of the study were examined from the perspective of Türkiye, no causality relationship was found between the variables.